Design of Academic Information System and New Student Admission System (PPDB) Based on Website at SMP Swasta Delisha with Prototype Model Approach - Taufik, Muhammad; Sarumaha, Demonius; Amir, Saiful (Devitara Innovations, 2025)
Advances in information technology have encouraged educational institutions to adopt digital systems to improve operational efficiency and service quality. SMP Swasta Delisha currently does not have a website-based system, so the New Student Admissions (PPDB) process and information delivery are still done manually. This manual approach leads to inefficiencies and increases the risk of administrative errors. This study aims to design and develop a website-based information system that includes online registration features, school profile information, and important announcements. The system development uses the Prototype Model method, which is iterative and flexible, allowing the system to be built according to user needs through direct feedback. The results of this study are expected to help SMP Swasta Delisha in improving the efficiency of the PPDB process, expanding the reach of information, and providing better services to prospective students and the wider community.